STRATEGI PEMASARAN TERHADAP OMZET PENJUALAN DI UKHUWAH GROSIR PADALARANG BANDUNG BARAT - Yulyanti, Dini; Ma’mun, Saepul; Sundari, Asri (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2024)
This research is motivated by the importance of marketing strategies in increasing sales turnover in the wholesale sector. Ukhuwah Grosir Padalarang West Bandung is the object of research to examine the extent to which marketing strategies affect the level of sales turnover. This study uses a quantitative approach with a survey method conducted through the distribution of questionnaires to consumers. The research population consisted of 50 consumers, who were also respondents using the census sample technique. The results of the descriptive analysis show that the variables of marketing strategy and sales turnover are in the high category. Furthermore, linear regression analysis shows that there is a significant relationship between marketing strategy and sales turnover. Marketing strategies contribute to explaining the variation in sales turnover, although most of them are still influenced by other variables that have not been studied. Further analysis shows that the improvement of marketing strategies has a positive impact on the increase in sales turnover, which illustrates the contributing relationship between the two variables. This study concludes that marketing strategy has a significant influence on increasing sales turnover at Ukhuwah Grosir Padalarang West Bandung. These findings underscore the importance of implementing effective marketing strategies to drive sales growth in the wholesale sector.